When we sold God's eye : diamonds, murder, and a clash of worlds in the Amazon - Cuadros, Alex (Grand Central Publishing, Hachette Book Group, 2024)
"The unbelievable true story of the Cinta Larga, a tribe first contacted by Westerners in the 1960s, who came to run an illegal diamond mine in the depths of the Amazon. Growing up in a remote corner of the world's largest rainforest, Pio, Maria, and Oita learned to hunt wild pigs and tapirs, gathering Brazil nuts and açaí berries from centuries-old trees. Then the first highway pierced through, ranchers, loggers, and prospectors invaded, and they lost their families to terrible new weapons and diseases. Pushed by the government to assimilate, they struggled to figure out their new, capitalist reality, discovering its wonders as well as its horrors. They ended up forging an uneasy symbiosis with their white antagonists--until decades of suppressed trauma erupted into a massacre, an act of retribution that made headlines across the globe. Based on six years of immersive reporting and research, WHEN WE SOLD GOD'S EYE tells a unique kind of adventure story, one that begins with a river journey by Teddy Roosevelt and ends with smugglers from Antwerp and New York City's Diamond District. It's a story of survival against all odds; of the temptations of wealth and the dream of prosperity; of a vital ecosystem threatened by the hunger for natural resources; of genocide and revenge. It's a story as old as the first European encounters with Indigenous people, playing out in the present day. But most of all, it's about a few startlingly clever individuals and their power to adapt and even thrive in the most unlikely circumstances"--